THE EFFICIENCY OF FLY ASH AND CEMENT SLAG TO DEVELOPMENT BUILDING (GEOMATE Journal, 2019)
In world construction, the construction of high-rise buildings almost entirely uses concrete. This study uses fly ash and cement slag as a cement substitute as a reduction in cement requirements. This is due to the limited amount of cement in the market and the binding function of cement and the increasing cement prices. The use of fly ash and cement slag is toxic hazardous waste material that must be handled so that it can be used properly. From the results of the age strength of concrete 1-3 days, the compressive strength of fly ash is higher than that of cement slag but from a mixture of 28 days, it reaches 100% in accordance with the specified standard. In this laboratory test for the use of fly ash and slag cement, 50%, in the future it is necessary to research that the use of fly ash and slag cement can be up to 70% so that the use of fly ash material and cement slag can replace the function of concrete mixed cement as a binder of coarse and fine material to get concrete compressive strength with specified standards. Production costs can be minimized so that if this applied can avoid the company from potential billions/year losses.